The Effect of Addition of Stone Ash to Shear Strength of Clay Soil in Suruh Trenggalek - Fauzie Nursandah; Fianca Nimas Yamada Puteri; Agata Iwan Candra; Yosef Cahyo Setianto Poernomo; Muhammad Heri Nastotok (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2021)
The land is one of the places where a building is built, so the structure depends on the ground’s strength. Clay soil is a type of has a low bearing capacity. Therefore it is necessary to conduct research that can increase soil bearing capacity. Rock ash is an artificial aggregate obtained from the by-products of a stone crusher or cement-factory. This study’s purpose is, namely, alarm and shear control of clay with the addition of rock ash. The clay soil used comes from the Trenggalek area. The percentage of adding agate is 0%, 10%, 20%, and 30% of the weight of the clay. The results showed that obtained were at a percentage of 30% with Liquid Limit value of 39.00%, Plastic Limit 29.00% and Plastic Index of 10.00%. In the Direct Strong Test, clay soil with the addition of 30% of the rock tested the maximum increase in shear stress of 0.486 with a shear angle of 40 ° and a decrease in the cohesion of 0.100 kg/cm². This shows that clay soil, which can be categorized as montmorillonite soil with the addition of rock ash, can increase the stability of the clay soil.